Surface hardening of Zr-based metallic glass via laser surface alloying with silicon powder. (November 2022) - Zhang, Di; Qian, Yongfeng; Zhang, Lin; Huang, Hu; Yan, Jiwang
Abstract: Increasing the hardness and wear resistance of metallic glasses (MGs) is beneficial to prolong their service life in highly aggressive environments. For the purpose of achieving surface hardening, in this work, laser surface alloying technology was employed to modify Zr-based MG with silicon powder as the pre-placed powder. The experimental results showed that the laser alloyed layer with thickness of several tens of micrometers was generated on the MG substrate. The surface hardness of the laser alloyed layers ranged from 11.34 to 17.97 GPa, which was significantly higher than that of the as-cast MG surface (6.36 GPa). Furthermore, the scratch resistance of the laser alloyed layer was improved compared to the as-cast sample. The chemical composition analysis indicated that the laser alloyed layer was mainly composed of in-situ formed ZrSi2 phase and residual Si, and these hard phases were responsible for the high hardness of the laser alloyed layer. Graphical abstract: Image, graphical abstract